2014
DOI: 10.1177/2048872614521756
|View full text |Cite
|
Sign up to set email alerts
|

Additive diagnostic and prognostic value of Bioelectrical Impedance Vector Analysis (BIVA) to brain natriuretic peptide ‘grey-zone’ in patients with acute heart failure in the emergency department

Abstract: While in the overall population BIVA did not increase diagnostic accuracy provided by BNP, in AHF patients a quantitative evaluation of fluid congestion obtained by BIVA at the time of emergency department arrival provides significant additive diagnostic and 30-day prognostic value to BNP, particularly in the BNP 'grey-zone'. This could lead to a better management of these patients with possible improvement in reducing subsequent cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
3
37
0
1
Order By: Relevance
“…We also found that BIVA had significant prognostic value for death for each considered follow-up time. This is not surprising and confirms previous study of our group, we also demonstrated additive value for AHF risk stratification of BIVA + BNP [8, 9]. The most important of our opinion results of our study is that the combination of BIVA + GAL3 increases the prognostic value for death and also for rehospitalization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that BIVA had significant prognostic value for death for each considered follow-up time. This is not surprising and confirms previous study of our group, we also demonstrated additive value for AHF risk stratification of BIVA + BNP [8, 9]. The most important of our opinion results of our study is that the combination of BIVA + GAL3 increases the prognostic value for death and also for rehospitalization.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, within subjects referring to the Emergency Department (ED) for AHF, BIVA has been demonstrated to be able to identify people at high risk for short-term mortality [8, 9]. In consideration of the two different aspects of GAL3 and of BIVA (the first is a fibrosis marker, and the second is a dynamic marker of congestion), we decided to evaluate in this study the degree of congestion correlated to that of fibrosis in AHF patients alone or together for the prediction of events.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in patients with CHF, BNP levels can be elevated; and it is harder to determine whether dyspnea symptoms are related to HF exacerbation or another extracardiac factor. In such cases, BIVA measurement could offer a complementary means for AHF diagnosis in the ED where cardiac ultrasound scan is not readily available as Di Somma et al [31] tried to show. In their study, BIVA did not increase diagnostic accuracy provided by BNP.…”
Section: Discussionmentioning
confidence: 97%
“…In a phase II trial, treatment guided by lung impedance (assessed using external electrodes) reduced heart failure hospitalizations 13. In addition, bioimpedance measures have been suggested as an adjunctive test for patients presenting with dyspnea at the emergency department, to identify heart failure patients when other tests are equivocal 14, 15. Whether the information obtained from impedance measures in patients with established heart failure translates into improved outcomes is, however, uncertain 13, 16, 17…”
Section: Discussionmentioning
confidence: 99%